DÁSTANLARDAǴÍ MIFOLOGIYALÍQ MOTIVLER HÁM OLARDÍŃ KÓRKEMLIK XÍZMETÍ (Edige dástanı mısalında) - Reymova, D. (SCIENCE and SOCIETY, 2023)
The article discusses the role of the mythical motif in the development of the plot in heroic novels. Also, the relationship between the motive and the plot is analyzed.